Osteochondral tissue engineering: nanotechnology, scaffolding-related developments and translation - Oliveira, Joaquim M. (2018)
In the last few years, osteochondral tissue engineering has shown an increasing development in advanced tools and technologies for damaged underlying subchondral bone and cartilage tissue repair and regeneration. Considering the limitation of articular cartilage to heal and self-repair, new therapeutic options are essential to develop approaches based on suitable strategies made of appropriate engineered biomaterials. This book overviews the most recent developments in the field of osteochondral tissue engineering, and presents challenges and strategies being developed that face not only bone and cartilage regeneration, but also establish osteochondral interface formation, in order to translate it into a clinical setting. Topics embrace biomaterials advances in osteochondral tissue engineering, namely natural, synthetic, and bioceramics-based materials, nanotechnology approaches, as well as advanced processing methodology underlying tissue-engineered scaffolding development, such as 3D bioprinting, electrospinning, and supercritical fluid technology. Hydrogel systems for osteochondral applications are also detailed thoroughly. It also maximizes the reader insights into translational research and turning research into products, clinical trials and management of osteochondral lesions, and commercially available products. This is an ideal book for biomedical engineering students and a wide range of established researchers and professionals working in the orthopedic field.